Taiwan's sovereignty under UN Charter Article 2 (4) and Article 1 of Montevideo Convention on the Rights and Duties of States - Zivtiņš, Eduards (Riga Graduate School of Law, 2023)
This undergraduate research investigates Taiwan's sovereignty claim's legal foundation and assesses whether it complies with the UN Charter and the Montevideo Convention. On the subject of sovereignty, the perspectives of Taiwan's citizens and officials are examined, along with the nations that back Taiwan's claim. Along with case law on Kosovo and Palestine, the impact of laws and regulations on Taiwan's sovereignty is also discussed. This thesis seeks to offer a thorough knowledge of Taiwan's sovereignty claim and its legal ramifications in the international community by looking at these distinct issues.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Sovereignty; the United Nations; UN Charter; Montevideo Convention; Taiwan